Factors detrimental to work productivity and daily activities in systemic lupus erythematosus patients – Analysis of the German LuLa study. (October 2021) - Kernder, Anna; Düsing, Christina; Richter, Jutta; Brinks, Ralph; Fischer-Betz, Rebecca; Winkler-Rohlfing, Borgi; Aringer, Martin; Schneider, Matthias; Chehab, Gamal
Objective: The aim of this study was to identify factors associated with impaired work productivity and impaired daily activities in patients with systemic lupus erythematosus (SLE). Methods: The LuLa study is a longitudinal patient-reported study. Beyond sociodemographic data, work productivity, daily activities and fatigue, several other clinical outcome parameters (e.g. mental health–related quality of life and physical functioning, disease activity, damage and pain) were surveyed with validated questionnaires. The effects of confounders on work productivity (WPAI 2) and daily activity domains (WPAI 4) were studied by multivariate regression analysis. Results: A total of 585 patients completed the questionnaire of whom 259 were employed and analysed. The median impairment in work productivity (WPAI 2) was 20% (Q1–3 0–40), and the median impairment in daily activities (WPAI 4) was 30% (Q1–3 10–50%). Multivariate regression analysis revealed that fatigue, pain, disease activity and health-related quality of life affected WPAI 2 and 4. Furthermore, we observed distinct synergistic effects of fatigue, disease activity and pain on both work productivity and daily activities: a higher impact of fatigue was associated with the reported extent of pain or disease activity. Conclusion: In employed patients with SLE, impaired work productivity and impaired daily activities were frequently reported. Fatigue, pain, disease activity and health-related quality of life demonstrated a detrimental impact, with a synergistic effect of fatigue, disease activity and pain. Hence, both optimized pain management and targeted immunomodulatory therapy are important for preserving active participation in life among patients with fatigue.